2020
DOI: 10.14639/0392-100x-n0608
|View full text |Cite
|
Sign up to set email alerts
|

Total thyroidectomy versus lobectomy: surgical approach to T1-T2 papillary thyroid cancer

Abstract: SUMMARY The incidence of papillary thyroid carcinoma, which accounts for 80-90% of all thyroid cancers, has recently been increasing. The current study aimed to compare the oncological and functional outcomes of total thyroidectomy (TT) and thyroid lobectomy (TL). To this end, a retrospective single-centre cohort study involving a tertiary care institution was conducted. Data regarding demographics, clinicopathology and postoperative complications from 586 patients with papillary thyroid cancer trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(39 reference statements)
2
6
0
Order By: Relevance
“…This restriction is largely due to the high postoperative complications rate after thyroid surgery plus lymph node dissection performed in centers with limited experience. Indeed, in high-volume centers, it seems that prophylactic central lymph node dissection doesn’t influence the postoperative complications rate, as confirm our results and other published papers [ 67 , 68 , 73 , 74 , 75 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This restriction is largely due to the high postoperative complications rate after thyroid surgery plus lymph node dissection performed in centers with limited experience. Indeed, in high-volume centers, it seems that prophylactic central lymph node dissection doesn’t influence the postoperative complications rate, as confirm our results and other published papers [ 67 , 68 , 73 , 74 , 75 ].…”
Section: Discussionsupporting
confidence: 92%
“…In most cases, only a less-radical surgical treatment, ultrasound-guided minimally invasive treatments, or an observational approach alone is recommended. Some authors have underlined that observation alone or surgery with conservative treatment (lobectomy) should be performed for low-risk tumors if they show neither unfavorable features nor the clinical suspicion of nodal metastases [ 12 , 29 , 68 ]. Recently, in some centers, minimally invasive treatments have been successfully used in the treatment of PTMCs as an alternative to active surveillance, in cases with no suspected LNM and no evidence of capsular involvement [ 27 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the H-P-T axis damage, hypocalcemia and vitamin D deficiency may also be associated with adverse IVF/ICSI outcomes. Filippo et al reported a nearly 3-fold higher hypocalcemia risk in patients who underwent total thyroidectomy than in patients who underwent lobectomy [ 18 ]. Vitamin D plays a pivotal role in regulating calcium metabolism, and a recent study showed a significant association between postoperative hypocalcemia and low preoperative vitamin D levels in patients after total thyroidectomy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer is one of the most rapidly increasing cancers globally, and papillary thyroid cancers (PTCs) make up 80 to 90% of this incidence (1). Until recently, the standard treatment for thyroid cancer of any size was total thyroidectomy; however, a robust literature has shown equivalent outcomes with total thyroidectomy and thyroid lobectomy, leading the American Thyroid Association (ATA) and other associations to recommend thyroid lobectomy for PTCs measuring up to 4 cm (1,2).…”
Section: Summary Backgroundmentioning
confidence: 99%